Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1159/000151251
|View full text |Cite
|
Sign up to set email alerts
|

Is Conventional Endoscopic Identification of Non-Erosive Reflux Disease Adequate?

Abstract: Non-erosive reflux disease is defined as the presence of troublesome reflux-associated symptoms in the absence of mucosal breaks at endoscopy. Given the fact that the majority of patients with reflux symptoms will have a normal endoscopy, efforts are underway to determine if new endoscopic techniques can identify changes heretofore invisible at the time of standard white light endoscopy. However, for any new endoscopic technology to be useful, the grading system it uses must be accurate, reproducible, easy to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Several other studies confirm this thesis. As Falk showed in their overview, it is difficult to grade NERD patients even with the use of most recent endoscopic techniques . Studies performed in Japan using high‐resolution endoscopy revealed several inflammatory lesions in NERD patients, but similar lesions were found in the control population as well …”
Section: Discussionmentioning
confidence: 99%
“…Several other studies confirm this thesis. As Falk showed in their overview, it is difficult to grade NERD patients even with the use of most recent endoscopic techniques . Studies performed in Japan using high‐resolution endoscopy revealed several inflammatory lesions in NERD patients, but similar lesions were found in the control population as well …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, current magnification endoscopy requires substantial expertise to obtain and interpret endoscopic images, which has limited its widespread acceptance. Therefore, the usefulness of magnification endoscopy and NBI in diagnosing GERD, so far, remains unclear . The unique advantage of AFI over magnifying NBI is the simple criterion of one or more longitudinal purple lines > 1 cm.…”
Section: Discussionmentioning
confidence: 99%
“…These GERD‐related cellular changes have prompted attempts to utilize techniques such as magnification endoscopy and narrow band imaging (NBI) to diagnose GERD. However, they are not widely utilized due to the limitations of lack of clearly defined diagnostic criteria, problematic inter‐observer agreements, or being time consuming …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Techniques that are currently under investigation include high-resolution endoscopy, magnifying endoscopy, chromoendoscopy, narrowband imaging, and confocal endomicroscopy. All of these new techniques can identify minimal abnormalities and differentiate them from SS-CLE in a superior manner to standard white light endoscopy [31], so those methods may solve this problem in the future.…”
Section: Discussionmentioning
confidence: 99%